WEBSITE DESIGNING PRACTICAL INFORMATION ON INFORMATION SYSTEMS LABORATORY STMIK JAKARTA STI&K USING PHP & MYSQL - Muhammad Muhtar; Marzuki Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Laboratory is a tool to practice the theory acquired in class and outside class. With goodteaching and training at the lab will prove that the theory was right or wrong is obtained,and results can be developed by praktikan practicum. To be able to implement goodteaching, appropriate teaching materials such as experimental module and practicalquestions are organized. By designing and creating a website and put them into a server,so it can be accessed by the praktikan with faster and easier learning process on lab work.Therefore, using PHP scripts in designing and making the information dynamic webbasedpracticum, and MySQL as database server, data maintenance is expected tobecome easier.